Adaptive radiation of Darwin's finches revisited using whole genome sequencing. (25th November 2015) - Almén, Markus Sällman; Lamichhaney, Sangeet; Berglund, Jonas; Grant, B. Rosemary; Grant, Peter R.; Webster, Matthew T.; Andersson, Leif
Abstract : We recently used genome sequencing to study the evolutionary history of the Darwin's finches. A prominent feature of our data was that different polymorphic sites in the genome tended to indicate different genetic relationships among these closely related species. Such patterns are expected in recently diverged genomes as a result of incomplete lineage sorting. However, we uncovered conclusive evidence that these patterns have also been influenced by interspecies hybridisation, a process that has likely played an important role in the radiation of Darwin's finches. A major discovery was that segregation of two haplotypes at the ALX1 locus underlies variation in beak shape among the Darwin's finches, and that differences between the two haplotypes in a 240 kb region in blunt and pointed beaked birds involve both coding and regulatory changes. As we review herein, the evolution of such adaptive haplotypes comprising multiple causal changes appears to be an important mechanism contributing to the evolution of biodiversity. Abstract : Whole genome studies, when combined with field data, provide a powerful method of investigating evolution. We review an example with two discoveries in Darwin's finches. Interspecific hybridisation has occurred throughout the radiation, and involved a locus encoding the ALX1 transcription factor that controls variation in beak shape and hence diets.